2020
DOI: 10.3390/ijms21155472
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated Immunoglobulins for the Treatment of Immuno-Inflammatory Diseases

Abstract: Immunoglobulins are the potent effector proteins of the humoral immune response. In the course of evolution, immunoglobulins have formed extremely diverse types of molecular structures with antigen-recognizing, antigen-binding, and effector functions embedded in a single molecule. Polysaccharide moiety of immunoglobulins plays the essential role in immunoglobulin functioning. There is growing evidence that the carbohydrate composition of immunoglobulin-linked glycans, and especially their terminal sialic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 130 publications
(173 reference statements)
1
17
0
Order By: Relevance
“…In fact, the multiple regression statistics showed an appreciable advantage of such a combination compared with the The reasons for changes in the sialylation of anti-E2 and anti-glycan Abs observed in this study remain yet unclear. It is well accepted that sialylated Igs have anti-inflammatory activity [4,13,35,36]. Alterations of Abs glycosylation in autoimmunity is a well-documented fact and the low level of IgG sialylation is usually associated with increased inflammation [6,7,10,16].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the multiple regression statistics showed an appreciable advantage of such a combination compared with the The reasons for changes in the sialylation of anti-E2 and anti-glycan Abs observed in this study remain yet unclear. It is well accepted that sialylated Igs have anti-inflammatory activity [4,13,35,36]. Alterations of Abs glycosylation in autoimmunity is a well-documented fact and the low level of IgG sialylation is usually associated with increased inflammation [6,7,10,16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was demonstrated that glycosylation of IgG Fc fragment importantly modulated IgG phagocytic activity and cytotoxicity, thus affecting its anti-inflammatory activity. In addition, IgG hypoglycosylation was associated with inflammatory immune-response in rheumatoid arthritis and collagen-induced arthritis ( 23 ). Another form of post-translational non-enzymatic glycosylation is called glycation: it is accounted by glucose and free amino groups of lysine residues and determines the formation of advanced glycation end products (AGEs) ( 24 ).…”
Section: Ig Mediates Anti-inflammatory Activitymentioning
confidence: 99%
“…Another form of post-translational non-enzymatic glycosylation is called glycation: it is accounted by glucose and free amino groups of lysine residues and determines the formation of advanced glycation end products (AGEs) ( 24 ). AGEs and their receptors (RAGE) are associated to different pathologies with important inflammatory background, such as atherosclerosis, diabetes and muscular disease ( 23 ). According to experimental evidences showing that the enrichment in terminal sialic acid of Ig residues could increase of more than 10-fold the anti-inflammatory activity of the preparation ( 25 ), modulation of glycosylation was used to develop therapeutic tools, as in autoimmune pathologies where high galactosylated/sialylated IgG antibodies blocked pro-inflammatory immune responses ( 26 ) or in rheumatoid arthritis, nephritis, lupus and sepsis ( 27 ).…”
Section: Ig Mediates Anti-inflammatory Activitymentioning
confidence: 99%
“…In order to quantitatively evaluate the complexity of coronary artery obstructions, preoperative SYNTAX scores were calculated for all patients. Patients were classified into three groups based on their SYNTAX score values using cut-offs from the US/European guidelines [low ≤22 (n = 34), intermediate [23][24][25][26][27][28][29][30][31][32] (n = 10), and high score >33 (n = 4)] (13,14). Moreover, information on occlusion of proximal RCA was also collected in order to perform subanalysis correlating proximal RCA occlusion and gene expression of RAA.…”
Section: Quantitative and Qualitative Patient Categorizationsmentioning
confidence: 99%